Marketization beyond Neoliberalization: A Neo-Polanyian Perspective on China's Transition to a Market Economy - Zhang, Jun (Environment and Planning A, 2013)
This paper proposes a neo-Polanyian framework of neoliberalization-as-marketization for understanding geohistorically embedded marketization based on five interlinked theoretical conceptualizations: embedded marketization, hybrid integration, double movement, active society, and qualitative state. I argue that this framework can be useful to supplement existing theorizing of neoliberalism, and to facilitate comparative case studies across vastly differently contexts. This framework is then taken to analyze China's post-Mao transition to a market economy. I argue that China's gradualist transition from a centrally planned economy to a mixed economy has been maneuvered by a self-regulating party-state (dis)embedded in a deactivated (active) society. Due to the existence of multiple veto players and intraparty ‘double movement’, the marketization was able to be mostly socially progressive until 1993. However, it was no longer the case when the ‘socialist market economy’ was enshrined and, without political liberalization, the Chinese version of neoliberalization has become even bleaker than elsewhere.
Geography
Keywords: China; double movement; marketization; neo-Polanyian; neoliberalization